MRI-Derived Radiomics to Guide Post-operative Management for High-Risk Prostate Cancer - Bourbonne, Vincent; Vallières, Martin; Lucia, François; Doucet, Laurent; Visvikis, Dimitris; Tissot, Valentin; Pradier, Olivier; Hatt, Mathieu; Schick, Ulrike (Frontiers in Oncology, 2019)
Purpose: Prostatectomy is one of the main therapeutic options for prostate cancer (PCa). Studies proved the benefit of adjuvant radiotherapy (aRT) on clinical outcomes, with more toxicities when compared to salvage radiotherapy. A better assessment of the likelihood of biochemical recurrence (BCR) would rationalize performing aRT. Our goal was to assess the prognostic value of MRI-derived radiomics on BCR for PCa with high recurrence risk. Methods: We retrospectively selected patients with a high recurrence risk (T3a/b or T4 and/or R1 and/or Gleason score>7) and excluded patients with a post-operative PSA>0.04ng/mL or a lymph-node involvement. We extracted IBSI-compliant radiomic features (shape and first order intensity metrics, as well as second and third order textural features) from tumors delineated in T2 and ADC sequences. After random division (training and testing sets) and machine learning based feature reduction, an univariate and multivariate Cox regression analysis was performed to identify independent factors. Correlation with BCR was assessed using AUC and prediction of biochemical relapse free survival (bRFS) with a Kaplan-Meier analysis. Results: 107 patients were included. With a median follow-up of 52.0 months, 17 experienced BCR. In the training set, no clinical feature was correlated with BCR. One feature from ADC (SZEGLSZM) outperformed with an AUC of 0.79 and a HR 17.9 (p=0.0001). Lower values of SZEGLSZM are associated with more heterogeneous tumors. In the testing set, this feature remained predictive of BCR and bRFS (AUC 0.76, p=0.0236). Conclusion: One radiomic feature was predictive of BCR and bRFS after prostatectomy helping to guide post-operative management.